A genre-instantiation approach to teaching English for Specific Academic Purposes: Student writing in Business, Economics and Engineering. (22nd February 2016) - Gardner, Sheena
Abstract : This paper introduces five linked resources and demonstrates, with a focus on Business, Economics and Engineering, their use in a novel genre-instantiation approach to teaching academic writing. The resources centre on the British Academic Written English (BAWE) corpus. They are: (1) published research literature that investigates the student assignment genres and registers; (2) descriptions of the contents of the corpus; (3) the BAWE corpus itself, which can be freely searched by teachers and learners; (4) online teaching materials based on the above; and (5) lesson plans from EAP teachers who use these materials in their teaching of presessional and in-sessional academic English. The genre instantiation approach to teaching academic writing builds on two central principles: the identification of key genres for target discipline-levels, and the exemplification of these through instances of successful student writing. This enables teachers to develop programmes that raise genre awareness, where learners can engage with instances from across specific topics, courses, levels and disciplines. The genre-instantiation approach is illustrated here with specific reference to Business Case Studies, Economics Essays and Engineering Methodology Recounts.